Mulheres, proibicionismo e resistências: lutas pela reprodução social da vida em meio a guerra às drogas no Brasil e na Colômbia - Santos, Aila Fernanda dos (2024)
This thesis aims to unveil the expressions of class struggle that are produced through integrated processes of social reproduction and political organization as forms of women's resistance to drug prohibition in Brazil and Colombia, using the Social Reproduction Theory (SRT) as its analytical framework. Grounded in the narratives of Black, Indigenous, and peasant women, it seeks to understand the specificities and impacts of the war on drugs on women's lives in each territory, as well as the forms of struggle and resistance organized by social movements and organizations, emphasizing a unitary perspective of these struggles. Adopting a theoretical-methodological approach based on totality, the research highlights the importance of moving beyond a restricted perspective of the working class and class struggle, acknowledging its diversity concerning race/ethnicity, gender, and territory. The study demonstrates how capitalism, as a social relation, intertwines the legal and illegal as a product of its accumulation dynamics. Methodologically, this is a militant, qualitative, and sentipensante research conducted with nine participants from Colombia and ten participants from Brazil. The research instruments included exploratory and semi-structured interviews, participant observation, and field diaries. The main findings reveal that the prohibitionist ideology, materialized in the war on drugs, exposes the relationship between the expanded reproduction of capital and the social reproduction of the labor force and life, challenging the apparent separation between production-reproduction and legal-illegal spheres. This operates as a "war-driven super-exploitation of the labor force" within the illegal market. Thus, illegality conceals particular forms of exploitation and oppression in each territory: in Colombia, it disproportionately affects peasant, Afro-Colombian, Indigenous, and migrant women, while in Brazil, it targets poor, Black, migrant, and peripheral women, subjecting them to riminalization and stigmatization. Regarding the agendas of social movements in both countries, Brazil stands out as the main proponent of anti[1]prohibitionist feminism, which emerges as a unifying strategy of struggles. In contrast, Colombia focuses on the implementation of the Final Peace Agreement, especially the points on “Comprehensive Rural Reform” and the “Solution to the Problem of Illicit Drugs.” Therefore, while these particularities in naming struggles and resistances are evident, they converge into an anti-prohibitionist and anti-capitalist project, in unity with the fight for the social reproduction of life as a whole